Integration of Gamification and Adaptive Learning in Augmented Reality Applications to Improve Elementary School Students' Mathematical Problem-Solving Creativity - Ita Fitriati; I Kadek Suartama; Muhammad Ghazali (Journal of Sustainable Educational Technology and Innovation, 2025)
Background of study: Mathematics learning in elementary schools still faces challenges in developing students' problem-solving creativity due to the dominance of procedural approaches and the limitations of contextual and personalized media. The integration of innovative learning technologies such as Augmented Reality (AR), gamification, and adaptive learning has the potential to create visual, engaging, and individualized learning experiences that encourage the exploration of creative strategies and solutions in mathematical problem-solving.Aims and scope of paper: This study aims to analyze the effectiveness of integrating gamification and adaptive learning concepts in the implementation of AR applications on improving elementary school students' creativity in solving math problems. The scope of the study focused on teaching math material on spatial figures to sixth-grade students at SDN Inpres Pali.Methods: The study used a quasi-experimental method with a pretest–posttest control group design. The research subjects consisted of two groups, namely the experimental group that used an adaptive gamification-based AR application and the control group that followed conventional learning. The research instruments included a mathematical problem-solving creativity test, an initial ability test, and a learning motivation questionnaire.Result: The results showed that students who learned using AR applications integrated with gamification and adaptive learning experienced a significantly higher increase in mathematical problem-solving creativity compared to the control group.Conclusion: The integration of gamification and adaptive learning in AR applications was effective in increasing the mathematical problem-solving creativity of elementary school students and had the potential to become an innovative digital learning model in elementary education.